Implementation of Tri Purusa Artha teachings in Coaching Hindu Young Generation - Sudarsana, I Ketut; Setyaningsih, Setyaningsih (Jayapangus Press, 2020)
This study aims to describe the implications of teachings tri purusa artha in coaching Hindu Young generation. The results showed that: (1) the understanding of the Hindu young generation in Desa Adat Ulakan about Tri Purusa Artha is already good because all informants can explain the meaning of Tri Purusa Artha and also explain the elements of Tri Purusa Artha theoretically. However, in implementing the three elements of Tri Purusa Artha, the Hindu young generation in the Desa Adat Ulakan could not implement it optimally. (2) The benefits of Tri Purusa Artha for young Hindu generation in the Ulakan Traditonal Village were a means of self-control and a way to achieve life goals in the form of jagadhita. (3) The obstacles faced in fostering Hindu young generation in Desa Adat Ulakan were the lack of facilities. Many young generations of Hindu was being indifferent. The appointed coaches or instructors still did not understand the interest of the young generation, they lived outside the village. Efforts in fostering the young generation of Hindus in Desa Adat Ulakan was done by providing counseling to the sekeha teruna to each banjar, forming skills, cooperating with village officers and village administrators, implementing Pasraman Hindu youths, forming sekeha gong and dance groups, pesantian teenagers groups, and providing sports fields.